A Mathematical Model for Blockchain Adoption in High-Risk Asset Management - Miftahol Arifin; Elisa Kusrini; Winda Nur Cahyo; Imam Djati Widodo (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2026)
This study develops and empirically validates a mathematical adoption model for blockchain-based information systems using an Extended Unified Theory of Acceptance and Use of Technology (UTAUT) framework. Previous blockchain adoption studies predominantly assessed behavioral determinants through isolated hypothesis testing, with limited efforts to integrate contextual factors into a unified structural model. To address this gap, the proposed framework incorporates blockchain-specific and organizational constructs, including trust and perceived security, operational resilience expectation, technology adaptability, and regulatory compliance, along with the core UTAUT dimensions. A quantitative, explanatory, and cross-sectional design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to estimate model parameters from survey data collected from 132 professionals operating in high-risk power plant asset management environments. The model explains 68.9% of the variance in behavior intention and 42.0% of actual system use. Trust and perceived security emerged as the strongest predictor of behavioral intention, followed by performance expectation and operational resilience expectation. The findings demonstrate the suitability of Extended UTAUT for mathematically representing the adoption behavior of blockchain in high-risk organizational settings and provide a transferable analytical framework for future studies of the adoption of blockchain-based information systems.